Paradiplomacy and biodiplomacy: Pluralistic forms of negotiating life - Sorondo Salazar, Dennis (Instituto de Estudios Internacionales, 2021)
The COVID-19 disease has conditioned our ways of being and living. Diplomacy, as a mediation of estrangement and as a pluralistic way of negotiating life, has not been immune to the changes generated by the pandemic. This article broadens the scope of diplomacy and paradiplomacy to introduce the concept of biodiplomacy and reveal the possibilities for analysis that it raises. The analysis of this concept generates multiple intersections and intermediate spaces from government techniques, ways of negotiating life and diplomatic practices. Biodiplomacy is subsequently used to analyse the pluralistic forms of mediation of estrangement and the negotiation of life that are manifested in liminal spaces. The author argues that biodiplomacy can serve to examine the way in which subjects "negotiate their life" and their "life is negotiated" together and in relation to other multiple organisms and beings.